Polish digit triplet test for auditory screening: development and initial evaluation - Ozimek, Edward; Kutzner, Dariusz; Sęk, Aleksander; Wicher, Andrzej (Archives of Acoustics, 2007)
The objective of this study was to develop and evaluate the Polish digit triplet test forspeech intelligibility screening. The first stage of the work deals with the preparation of the testand the recording procedure. The second part presents results of the digit triplets intelligibilitymeasurement and retest data. The test consists of 4 statistically equivalent and phonemicallybalanced lists, each containing 25 different triplets. The constant stimuli paradigm was usedto determine the digit triplet psychometric functions. Fifty otologically normal subjects tookpart in the measurements. The mean list-specific SRT and $S_{50}$ for Polish digit triplet testare −9.4 dB and 19.7%/dB, respectively, and correlate very well with analogous parametersobtained for German digit triplet test, i.e. −9.3 dB and 19.6%/dB. The Polish digit triplet testevaluated in retest experiments revealed high reliability and accuracy for a fast intelligibilityscreening.